Zero-dimensional carbon material composite modified fast-charging graphite and application thereof

CN122950442APending Publication Date: 2026-10-20CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611156283.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0005]第二,常规的改性手段大多仅停留在简单的物理附着层面(即在石墨外面“套一层壳”),无法对石墨核心的储能入口(即边缘的微观形貌)进行有效的调控

Benefits of technology

[0031](1)打破了常规碳包覆的局限,实现结构重组: 现有技术常认为碳包覆仅能提供物理隔离。而本发明出乎意料地发现,利用碳量子点尺寸极小且含丰富官能团的特性,在特定温度下剧烈热解与收缩产生的局域应力,能原位形成超薄低阻的无定形碳层。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to the field of nanomaterials technology, and more particularly to a zero-dimensional carbon material composite modified fast-charging graphite and its applications. When carbon quantum dots are used, the modified fast-charging graphite material has a crystalline graphite core inside, with its outer surface and edges coated with an ultrathin amorphous carbon layer with a thickness of 10 nm or less; furthermore, its edges exhibit lamellar curling and lattice distortion structures; the ultrathin amorphous carbon layer is formed by the conversion of carbon quantum dots. When fullerenes are used, the modified fast-charging graphite is obtained by uniformly mixing fullerenes with graphite and then sintering under a protective atmosphere. The product obtained by this invention exhibits excellent electrochemical reaction kinetics and interfacial structural stability, with abundant ion storage active sites and wide ion rapid diffusion channels, and can be widely used in various types of graphite anodes and energy storage fields. Furthermore, the preparation process of this invention is simple, requires no complex pretreatment, has strong universality, and can be mass-produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nano-carbon materials technology, and in particular to a zero-dimensional carbon material composite modified fast-charging graphite and its applications. Background Technology

[0002] Graphite is a highly crystalline carbon material consisting of multiple layers with sp... 2 Graphite is a hexagonal lattice of carbon atoms with a hybrid structure. Due to its excellent conductivity, structural stability, and low cost, graphite has been widely used in commercial lithium-ion battery anodes and various electrochemical energy storage fields. However, the highly ordered lattice structure of graphite results in a relative scarcity of defects and active sites on its surface; and ions can only be inserted from the edges of graphite sheets, leading to sluggish diffusion kinetics of ions (especially lithium ions at high rates or large-radius sodium / potassium ions) at the graphite interface. This severely limits its application performance in fast-charging and high-power-density devices. Therefore, improving the reaction kinetics of the graphite interface has become a research hotspot.

[0003] Engineering the microstructure of the surface and interface of graphite materials is an effective way to synthesize composite carbon materials with specific properties.

[0004] Currently, surface and interface microstructure engineering of graphite materials (such as constructing carbon coatings) is a common method to improve the electrochemical performance of these materials. However, existing surface modification technologies for graphite face two pressing challenges: First, traditional carbon coating processes (such as using macromolecular polymer precursors like pitch and phenolic resins) have significant limitations. Macromolecular precursors are difficult to coat uniformly at the nanoscale on the graphite surface, often resulting in excessively thick coatings or severe agglomeration after pyrolysis. Excessively thick coatings not only reduce the material's compaction density but also significantly increase the solid-phase diffusion distance and charge transfer impedance of energy storage ions penetrating the interface, thus blocking rapid lithium intercalation channels. Achieving nanoscale, low-impedance interfacial coatings that are strongly bonded to the graphite matrix remains a major technical challenge.

[0005] Second, conventional modification methods mostly remain at the level of simple physical adhesion (i.e., "coating" graphite with a shell), failing to effectively control the energy storage entry points of the graphite core (i.e., the microscopic morphology of the edges). The highly dense graphite edges hinder the rapid absorption and release of ions. Currently, there are few effective solutions for breaking the limitations of the perfect graphite lattice without compromising the overall structural stability of graphite, achieving the "reconstruction and transformation" of the edge structure, and thus opening up high-speed ion diffusion channels within.

[0006] Therefore, there is an urgent need to develop a novel composite modification method that can effectively overcome the limitations of dense edge lattices while achieving ultrathin, low-resistivity coating on graphite surfaces, thereby endowing the material with abundant active sites and broad, fast ion transport channels. Summary of the Invention

[0007] To address the technical problems mentioned above in the prior art (such as slow graphite interface dynamics and high impedance of existing coatings), this invention provides a zero-dimensional carbon material composite modified fast-charging graphite and its application.

[0008] This invention discloses a zero-dimensional carbon material composite modified fast-charging graphite. When modified with carbon quantum dots, the modified fast-charging graphite has a crystalline graphite core inside, and its outer surface and edges are coated with an ultrathin amorphous carbon layer. Furthermore, the edges of the modified graphite material exhibit lamellar curling and lattice distortion structures. The thickness of the ultrathin amorphous carbon layer is 1 nm to 10 nm, and the ultrathin amorphous carbon layer is transformed from carbon quantum dots.

[0009] When fullerene is used for modification, modified fast-charging graphite is obtained by uniformly mixing fullerene with graphite and then sintering it under a protective atmosphere.

[0010] Preferably, the present invention provides a zero-dimensional carbon material composite modified fast-charging graphite, wherein the thickness of the ultrathin amorphous carbon layer is 2nm-10nm, including thicknesses of 2nm-4nm, 2nm-6nm, 2nm-8nm, etc. Furthermore, the modified graphite material exhibits lamellar curling and lattice distortion structures at its edges; the ultrathin amorphous carbon layer is formed by the conversion of carbon quantum dots.

[0011] The parameters of the lattice distortion structure satisfy at least one of the following conditions:

[0012] (1) In the Raman spectrum of the modified graphite material, the intensity ratio (ID / IG) of the defect peak (D peak) to the graphitization peak (G peak) is 0.2 ~ 1.2, preferably 0.5 ~ 1.2;

[0013] (2) In the X-ray diffraction pattern of the modified graphite material, the interlayer spacing of the (002) crystal plane is 0.3350 nm ~ 0.3380 nm.

[0014] In this invention, the lattice distortion structure can broaden the insertion channels of energy storage ions, thereby reducing the resistance to ion migration.

[0015] The thickness of the ultrathin amorphous carbon layer is controlled to be 1 nm to 10 nm in this invention because: if there is no ultrathin amorphous carbon layer or the thickness is insufficient, the edges of the highly active distorted graphite will be directly exposed, leading to continuous decomposition of the electrolyte and deterioration of cycle life; if the amorphous carbon layer is too thick, it will drastically increase the solid-phase diffusion distance of ions and the interfacial charge transfer resistance, which will block the fast lithium intercalation channel and reduce the compaction density of the material.

[0016] This invention discloses a zero-dimensional carbon material composite modified fast-charging graphite, which is prepared through the following steps:

[0017] Zero-dimensional carbon material is mixed with graphite matrix in a set ratio to obtain a solid mixture; the solid mixture is placed in a protective atmosphere for high-temperature carbonization treatment to obtain zero-dimensional carbon material composite modified fast-charging graphite; the zero-dimensional carbon material is selected from at least one of carbon quantum dots and fullerenes.

[0018] When the zero-dimensional carbon material is carbon quantum dots, during high-temperature carbonization treatment, the carbon quantum dots undergo in-situ pyrolysis on the surface and edges of graphite, resulting in high-temperature composite modified graphite of carbon quantum dots.

[0019] In some embodiments of this application, the graphite matrix includes at least one of natural flake graphite, microcrystalline graphite, spherical graphite, mesophase carbon microspheres, or artificial graphite.

[0020] In some embodiments of this application, carbon quantum dots include undoped carbon quantum dots and / or heteroatom-doped carbon quantum dots; wherein the undoped carbon quantum dots mainly contain oxygen-containing functional groups on the surface, and the heteroatom-doped carbon quantum dots include carbon quantum dots doped with at least one element selected from nitrogen, sulfur, phosphorus or boron.

[0021] In some embodiments of this application, the precursors for preparing carbon quantum dots include at least one of citric acid, glucose, ascorbic acid, urea, thiourea, ethylenediamine, or biomass-derived carbon sources.

[0022] In some embodiments of this application, the mass ratio of the zero-dimensional carbon material to the graphite matrix is ​​(1:50) to (1:10), preferably 1:50 to 1:15, more preferably 1:50 to 1:20, and even more preferably 1:18 to 1:22, including 1:20.

[0023] In some embodiments of this application, solid-phase mixing is performed by mechanical grinding or ball milling in the mixing step, and the mixing time is 0.1 h-1 h.

[0024] In some embodiments of this application, the protective atmosphere includes one or more mixed gases selected from nitrogen, argon, or helium, with a gas flow rate of 50 mL / min to 200 mL / min.

[0025] In some embodiments of this application, the heating rate of the high-temperature carbonization process is 1°C / min. –1 ~10℃ min –1 .

[0026] In some embodiments of this application, in the high-temperature carbonization process, the carbonization temperature is 800°C to 1100°C, preferably 950°C to 1050°C, and more preferably 980°C to 1020°C, which of course includes 1000°C.

[0027] In some embodiments of this application, the carbonization time in the high-temperature carbonization process is 2h-6h.

[0028] In some embodiments of this application, the zero-dimensional carbon material composite modified fast-charging graphite is used as the negative electrode active material of an electrochemical energy storage device, which includes a lithium-ion battery, a sodium-ion battery, or a potassium-ion battery.

[0029] The zero-dimensional carbon material composite modified fast-charging graphite designed and prepared in this invention exhibits extremely superior rate performance when used in secondary batteries. When the zero-dimensional carbon material is carbon quantum dots, its rate performance is even more superior.

[0030] The beneficial effects achieved by this invention are as follows:

[0031] (1) Breaking the limitations of conventional carbon coating and realizing structural reorganization: Existing technologies often believe that carbon coating can only provide physical isolation. However, this invention unexpectedly discovered that by utilizing the characteristics of carbon quantum dots with extremely small size and rich functional groups, the local stress generated by violent pyrolysis and contraction at a specific temperature can form an ultrathin, low-resistivity amorphous carbon layer in situ.

[0032] (2) An ideal fast-charging structure of “disordered opening edge - highly crystalline core” was constructed: This micro-distortion structure with strictly defined parameters broadens the insertion channel of energy storage ions, reduces the ion diffusion barrier, improves the high-rate reaction kinetics of graphite materials, and at the same time retains the fast electron transport network and excellent structural stability inside graphite.

[0033] (3) The process is simple, requiring only simple solid-phase mechanical grinding and one-step pyrolysis, without the need for complex liquid-phase solvent dispersion or CVD equipment. It is highly compatible with existing graphite anode production lines and has extremely high potential for low-cost industrial mass production. Attached Figure Description

[0034] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.

[0035] Figure 1 The images shown are scanning electron microscope (SEM) and transmission electron microscope (TEM) images of carbon quantum dot high-temperature composite modified graphite, original graphite, and the product obtained after carbonizing the original graphite at 1000℃, according to Example 1 of the present invention.

[0036] Figure 2 The images show the Raman spectra of the products obtained in Example 1 and Comparative Examples 1-2 of this invention.

[0037] Figure 3 These are electrochemical performance characterization diagrams of the products obtained in Examples 1-3 and Comparative Example 1 of the present invention.

[0038] Figure 4 These are electrochemical performance characterization diagrams of the products obtained in Examples 4-6 of this invention.

[0039] Figure 5 The electrochemical performance characterization diagrams are for the products obtained in Examples 1 and 7-8 of this invention after being made into half-cells.

[0040] Figure 6 The electrochemical performance characterization diagrams are shown for the products obtained in Examples 9-10 of this invention after being made into half-cells.

[0041] Figure 7 The image shows the electrochemical performance characterization of the product obtained in Example 11 of this invention after it was made into a half-cell.

[0042] Figure 8 The images show the electrochemical performance of the products obtained in Example 1 and Comparative Example 1 after assembling a full cell.

[0043] Figure 1 In the image, Figures a and b are SEM images of carbon quantum dot-modified graphite at different magnifications, respectively; Figure c is a TEM image of carbon quantum dot-modified graphite (CQDs@G); Figures d, e, and f are SEM and TEM images of the original graphite sample after high-temperature carbonization at 1000℃ (G-1000℃), respectively; Figure g is a SEM image of the original graphite sample; Figure h is an image of a single particle of the original graphite sample; and Figure i is a TEM image of the original graphite sample. Figure 1The morphology of carbon quantum dot high-temperature composite modified graphite, the original graphite after high-temperature carbonization at 1000℃, and the original graphite can be seen. In particular, it can be seen that the thickness of the amorphous carbon layer of carbon quantum dot high-temperature composite modified graphite is about 2.5nm, while the original graphite and the original graphite after high-temperature carbonization at 1000℃ do not have an amorphous carbon layer generated.

[0044] from Figure 2 As can be seen, the ID / IG of the original graphite in Comparative Example 1 is 0.25, the ID / IG of the product in Comparative Example 2 is 0.33, and the ID / IG of the product obtained in Example 1 is 0.61.

[0045] from Figure 3 The rate cycling performance of the products obtained in Example 1, Example 2, Example 3, and Comparative Example 1 can be seen from the data.

[0046] from Figure 4 The rate cycling performance of the products obtained in Examples 4, 5, and 6 can be seen from the data.

[0047] from Figure 5 The rate cycling performance of the products obtained in Examples 1, 7, and 8 can be seen from the data.

[0048] from Figure 6 The rate cycling performance of the products obtained in Examples 9 and 10 can be seen from the data.

[0049] from Figure 7 The rate cycling performance of the product obtained in Example 11 can be seen from the data.

[0050] from Figure 8 The rate cycle performance of the products obtained in Example 1 and Comparative Example 1 after being assembled into a full battery can be seen from the data.

[0051] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation

[0052] It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.

[0053] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0054] In this invention, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying their relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined with "first" or "second" may explicitly or implicitly include at least one of that feature. Furthermore, the technical solutions of the various embodiments can be combined with each other, but only on the basis of being achievable by those skilled in the art. If the combination of technical solutions is contradictory or impossible to implement, such a combination of technical solutions should be considered non-existent and not within the scope of protection claimed by this invention.

[0055] Currently, there are many existing technologies for improving the electrochemical properties of graphite by coating its surface with polymers (such as pitch and resin), but the improvement effect is very limited. Traditional coatings are often too thick or uneven, which can easily increase the resistance to ion migration. At the same time, existing technologies cannot achieve ultra-thin coatings while specifically modifying the microstructure of the graphite edges to broaden ion transport channels. In addition, some existing technologies require complex liquid-phase solvent treatment for graphite modification, which is not only costly but also generates a large amount of waste liquid, lacking industrial applicability.

[0056] In view of this, this invention designs a high-temperature composite modified graphite with a special zero-dimensional carbon material and provides a low-cost, rapid, and efficient preparation method for this material. It also develops an application method that best reflects the advantages of this material. The zero-dimensional carbon material composite modified fast-charging graphite obtained after high-temperature composite modification using carbon quantum dots can be denoted as CQDs@G.

[0057] In this invention, the graphite matrix primarily provides a highly crystalline energy storage core and electron transport network, while carbon quantum dots and / or fullerenes mainly serve as surface modifiers and edge morphology inducers. Carbon quantum dots, with their extremely small physical size (typically nanometer-scale) and abundant surface oxygen- or heteroatom functional groups, readily undergo uniform van der Waals adsorption on the graphite surface. During high-temperature carbonization, the carbon quantum dots decompose in situ, forming a low-resistance, ultrathin amorphous carbon coating layer on the graphite surface. After optimization, a heterogeneous interface structure of "disordered open edges - highly crystalline core" is ultimately constructed.

[0058] In some embodiments, the graphite matrix includes, but is not limited to, at least one of natural flake graphite, microcrystalline graphite, spherical graphite, mesophase carbon microspheres, or artificial graphite. The above graphite materials possess highly ordered sp... 2 The hybrid carbon layer structure, as a matrix, can ensure that the composite material as a whole has excellent electrical conductivity and volumetric energy density.

[0059] In some embodiments, carbon quantum dots include undoped carbon quantum dots and / or heteroatom-doped carbon quantum dots. Undoped carbon quantum dots are preferred.

[0060] In one embodiment, the precursors for preparing carbon quantum dots include oxygen-containing organic small molecules such as citric acid, glucose, and ascorbic acid, or biomass-derived carbon sources. Undoped carbon quantum dots prepared from these precursors have a surface rich in oxygen-containing functional groups such as hydroxyl and carboxyl groups, exhibiting excellent dispersibility when mixed with graphite, and forming a defect-rich amorphous carbon layer after high-temperature carbonization.

[0061] In one embodiment, the precursors for preparing carbon quantum dots include heteroatom-containing compounds such as urea, thiourea, and ethylenediamine. Heteroatom-doped carbon quantum dots synthesized from these precursors (e.g., nitrogen, sulfur, phosphorus, or boron doped) can have their heteroatoms in situ incorporated into the amorphous carbon layer on the graphite surface during the high-temperature carbonization process, further providing additional electrochemical active sites and enhancing the adsorption kinetics for energy storage ions (such as lithium, sodium, and potassium ions).

[0062] In this invention, the mass ratio of zero-dimensional carbon material to graphite matrix is ​​(1:50) to (1:10). In some embodiments, the mass ratio can be any value within the range of (1:50) to (1:10), such as 1:50, 1:45, 1:40, 1:35, 1:30, 1:25, 1:20, 1:15, 1:12, or 1:10. Of course, 1:50 to 1:20 is also preferred.

[0063] At the above mass ratio, it can be ensured that carbon quantum dots form a uniform and moderately thick coating layer on the graphite surface and effectively induce edge curling. If the proportion of carbon quantum dots is too low, the modification effect will be insignificant and the ion channels cannot be effectively broadened; if the proportion of carbon quantum dots is too high, it may lead to an excessively thick amorphous carbon layer after pyrolysis or agglomeration, which will increase the diffusion resistance of ions and reduce the first coulombic efficiency of the material.

[0064] In some embodiments, solid-phase mixing is performed by mechanical grinding or ball milling for a mixing time of 0.1 h to 1 h. For example, the mixing time can be 0.1 h, 0.2 h, 0.3 h, 0.4 h, 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, or 1.0 h. Solid-phase mixing not only avoids the use of toxic or expensive solvents, but the mechanical shear force also helps to uniformly disperse and embed nanoscale carbon quantum dots on the surface and edges of micron-scale graphite particles, providing a prerequisite for subsequent uniform pyrolysis.

[0065] In some embodiments, the heating rate of the high-temperature carbonization treatment is 1°C / min. –1 ~ 10℃min –1 It can be 1℃min –1 2℃min –1 3℃min –1 5℃min –1 8℃min –1or 10℃min –1 A suitable heating rate can ensure the stable pyrolysis of carbon quantum dots and prevent the destruction of the graphite matrix structure due to the violent release of gas caused by excessively rapid heating.

[0066] In some embodiments, the carbonization temperature is 800℃ ~ 1100℃, and can be any temperature within the range of 800℃, 850℃, 900℃, 950℃, 1000℃, 1050℃, or 1100℃. The carbonization time is 2h-6h, and can be 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, or 6h.

[0067] Under the above heat treatment conditions, non-carbon elements (such as oxygen, hydrogen, etc.) in carbon quantum dots and / or fullerenes are fully released in gaseous form, and the carbon skeleton undergoes reconstruction and shrinkage.

[0068] In some embodiments, high-temperature carbonization is performed in a protective atmosphere, which can be at least one of argon, nitrogen, or helium. Under the protection of an inert atmosphere, the combustion loss of the graphite matrix and zero-dimensional carbon material with oxygen at high temperatures is effectively prevented, ensuring a high yield of the composite material.

[0069] This invention does not limit the equipment used for high-temperature carbonization. In some embodiments, tube furnaces, atmosphere furnaces, or rotary kilns are selected as heat treatment equipment. For example, using a tube furnace can make the solid mixture heat more uniformly, and make the in-situ pyrolysis and stress contraction reaction more thorough.

[0070] After optimization, the carbon quantum dot high-temperature composite modified graphite material (CQDs@G) developed in this invention can be observed by high-resolution transmission electron microscopy (HRTEM). The material exhibits obvious lamellar curling at the edges and is coated with an ultrathin amorphous carbon layer with a thickness of about 2 nm to 4 nm.

[0071] This zero-dimensional carbon-modified fast-charging graphite can be used as a negative electrode active material in electrochemical energy storage devices such as lithium-ion, sodium-ion, or potassium-ion batteries. Due to its non-uniform interface structure, it effectively lowers the activation energy barrier for ion intercalation. Electrochemical tests show that this material exhibits excellent charge-discharge capacity at a high rate of 6C. In particular, the carbon quantum dot-modified fast-charging graphite exhibits even better charge-discharge capacity at a high rate of 6C.

[0072] The zero-dimensional carbon material composite modified fast-charging graphite developed in this invention has both excellent interfacial reaction kinetics and structural stability. Moreover, the preparation process only requires solid-phase mixing and one-step calcination, without involving complex chemical processes. It has strong versatility and high efficiency, and is easily compatible with existing graphite anode industrial production lines, thus possessing great potential for large-scale production.

[0073] The technical solution of the present invention will be further described in detail below with reference to specific embodiments. It should be understood that the following specific embodiments are only used to explain the present invention and are not intended to limit the present invention.

[0074] Example 1

[0075] In this embodiment, the designed carbon quantum dot high-temperature composite modified graphite material (CQDs@G) is prepared through the following steps:

[0076] S10: 1 g of graphite material (such as natural flake graphite with a particle size of 1-10 μm) and 50 mg of carbon quantum dots (such as undoped carbon quantum dots derived from citric acid with a particle size of 1-10 nm) are placed in a mortar and mechanically ground and mixed for 0.5 h until uniformly mixed to obtain a carbon dot composite graphite precursor.

[0077] S20, the above 1.05 g precursor was placed in a porcelain boat and then pushed into the isothermal zone of a tube furnace. Under the protection of a flowing argon atmosphere (Ar, flow rate of 50 mL / min), it was heated at 5 °C for 1 min. –1 The furnace was heated at a rapid heating rate. When the temperature of the tube furnace reached 1000 °C, it was kept at a constant temperature for 2 hours to allow the carbon quantum dots to undergo in-situ decomposition and carbonization shrinkage at high temperature. After the reaction was completed, the furnace was naturally cooled to room temperature under argon protection, and the powder was collected to obtain the carbon quantum dot high-temperature composite modified graphite material (denoted as: CQDs@G-5%-1000).

[0078] Example 2

[0079] This embodiment follows the preparation method of Example 1, except that in step S10, the content of carbon quantum dots is 20 mg. All other steps and parameters remain the same as in Example 1, resulting in a modified graphite material (denoted as: CQDs@G-2%-1000).

[0080] Example 3

[0081] This embodiment follows the preparation method of Example 1, except that in step S10, the content of carbon quantum dots is 100 mg. All other steps and parameters remain the same as in Example 1, resulting in a modified graphite material (denoted as: CQDs@G-10%-1000).

[0082] Example 4

[0083] This embodiment follows the preparation method of Example 1, except that in step S20, the carbonization temperature is set to 800 °C. All other steps and parameters remain the same as in Example 1, resulting in a modified graphite material (denoted as: CQDs@G-5%-800).

[0084] Example 5

[0085] This embodiment follows the preparation method of Example 1, except that in step S20, the carbonization temperature is set to 900 °C. All other steps and parameters remain the same as in Example 1, resulting in a modified graphite material (denoted as: CQDs@G-5%-900).

[0086] Example 6

[0087] This embodiment follows the preparation method of Example 1, except that in step S20, the carbonization temperature is set to 1100 ℃. All other steps and parameters remain the same as in Example 1, resulting in a modified graphite material (denoted as: CQDs@G-5%-1100).

[0088] Example 7

[0089] This embodiment follows the preparation method of Example 1, except that in step S10, 50 mg of nitrogen-doped carbon quantum dots (N-CQDs) are used. All other steps and parameters remain the same as in Example 1, resulting in modified graphite material (N-CQDs @G-5%-1000).

[0090] Example 8

[0091] This embodiment follows the preparation method of Example 1, except that in step S10, 50 mg of nitrogen- and sulfur-doped carbon quantum dots (NS-CQDs) are used. The remaining steps and parameters are consistent with those of Example 1, resulting in a modified graphite material (denoted as: NS-CQDs @G-5%-1000).

[0092] Example 9

[0093] This embodiment designs a fullerene high-temperature composite modified graphite material (C60@G), which is prepared through the following steps:

[0094] S10: 1 g of graphite material (such as natural flake graphite with a particle size of 1-10 μm) and 50 mg of fullerene (C60) are placed in a mortar and mechanically ground and mixed for 0.5 h until uniformly mixed to obtain a fullerene composite graphite precursor.

[0095] S20, 1.05 g of the precursor was placed in a ceramic boat and then pushed into the isothermal zone of a tube furnace. Under the protection of a flowing argon atmosphere (Ar, flow rate 50 mL / min), the mixture was heated at a rate of 5 °C min⁻¹. When the temperature of the tube furnace reached 1000 °C, it was held at this temperature for 2 h, allowing the carbon quantum dots to undergo in-situ decomposition and carbonization shrinkage at high temperature. After the reaction was complete, the mixture was naturally cooled to room temperature under argon protection, and the powder was collected to obtain the fullerene high-temperature composite modified graphite material (denoted as: C60@G-5%-1000).

[0096] Example 10

[0097] This embodiment follows the preparation method of Example 9, except that in step S10, 125 mg of fullerene (C60) is used. All other steps and parameters remain the same as in Example 9, resulting in the fullerene-modified graphite material (denoted as: C60@G-12.5%-1000).

[0098] Example 11

[0099] This comparative example provides a carbon quantum dot composite graphite material that has not undergone high-temperature carbonization, and its preparation steps are as follows:

[0100] 1 g of graphite material and 50 mg of carbon quantum dots were placed in a mortar and mechanically ground and mixed for 0.5 h until homogeneous. Unlike the previous examples, this comparative example omits the subsequent high-temperature carbonization step in a tube furnace and directly collects the mixed powder as a control sample (denoted as: CQDs@G - uncarbonized).

[0101] Comparative Example 1

[0102] In this comparative example, pristine graphite was used as the benchmark for performance improvement, as pristine graphite does not contain an ultrathin amorphous carbon layer.

[0103] Comparative Example 2

[0104] In this comparative example, the original graphite sample carbonized at 1000℃ is used as Comparative Example 2. After carbonization at 1000℃, the original graphite did not have an ultrathin amorphous carbon layer.

[0105] Performance testing

[0106] The carbon quantum dot high-temperature composite modified graphite material (CQDs@G-5%-1000) obtained in Example 1 was characterized using a scanning electron microscope (SEM) with a magnification of 1 μm and a transmission electron microscope (TEM) with a magnification of 5 nm, respectively. The results are shown in the figure. Figure 1 .

[0107] The electrochemical performance of the products obtained in the examples and comparative examples was measured, and the results are shown in Table 1.

[0108] Table 1. Performance Comparison of Products Obtained from the Examples and Comparative Examples

[0109]

[0110] The electrochemical performance test conditions in Table 1 are as follows: constant temperature 25℃, ester-based electrolyte, current density from 0.1C to 6C, 1C = 372 mAh g⁻¹ –1 The full battery uses a lithium iron phosphate cathode, with current densities ranging from 0.1C to 40C, where 1C = 170mAh g. –1 .

[0111] Combination Figure 1 It can be known that:

[0112] The carbon quantum dot high-temperature composite modified graphite material (CQDs@G) prepared by the technology of this invention, namely Example 1, successfully constructed an "amorphous carbon coating-edge distortion" interface. At a high temperature of 1000 ℃, the expansion force and recombination stress generated by the pyrolysis of carbon quantum dots widened the graphite interlayer spacing, causing edge lamellar curling and distortion. Subsequently, the carbon quantum dots, transformed into amorphous carbon, formed strong C-C bonds with the distorted edges, forming a protective film on the outermost layer. At the same time, the originally dense graphite edges were transformed into open and topologically defect-rich ion transport channels, reducing the resistance to ion entry.

[0113] Based on the discharge specific capacity test results at 6 C (high current fast charging) in Table 1, we can see that:

[0114] Example 1 shows a high rate specific capacity of up to 83.5 mAh g. -1 It is unmodified pure graphite (Comparative Example 1, 41.8 mAhg). -1 The results show that the interface modification of this invention significantly improves the fast charging dynamics of lithium ions, which is about twice that of lithium ions.

[0115] Comparison of Example 1 with Examples 2 and 3 ( Figure 3 It can be seen that when the carbon quantum dot content drops to 2%, the specific capacity decreases significantly to 56.7 mAhg due to insufficient stress to induce sufficient edge distortion, incomplete coating, and over-coating. -1 With 19.2 mAh g -1 .

[0116] Temperature gradient experiments in Examples 1 and 4-6 Figure 4 This indicates that the carbonization temperature determines the degree of pyrolysis and stress release of the carbon points. Overall, 1000 ℃ (Example 1) shows the best effect on improving fast charging performance.

[0117] Comparison between Example 1 and Examples 7-8 ( Figure 5It can be seen that, when different types of carbon quantum dots (undoped CQDs, nitrogen-doped N-CQDs, and nitrogen-sulfur co-doped NS-CQDs) are used for modification, the modification effect of undoped CQDs (Example 1) is the best, which achieves 83.5 mAh g at 6 C. -1 The highest capacity was achieved by nitrogen-doped N-CQDs and NS-CQDs, which still exhibited higher capacities than pristine graphite, at 60.4 mAh g⁻¹. -1 and 69.4 mAh g -1 Graphite, on the other hand, has a capacity of 41.8 mAh g. -1 This further demonstrates that the specific carbon quantum dots selected in this invention have a significant effect on improving the fast-charging performance of batteries.

[0118] Comparison of Examples 9-10 with Comparative Example 1 ( Figure 6 It can be seen that, when modifying with different contents of fullerene (C60@G-5%-1000 and C60@G-12.5%-1000), the modification effect is the best with a C60 doping content of 5% (Example 9), which yields 53.89 mAh g at 6 C. -1 The highest capacity was achieved with a C60 doping content of 12.5% ​​(Example 10, 53.58 mAh g). -1 Both still exhibited higher capacities than the original graphite (Comparative Example 1), with graphite having a capacity of 41.8 mAh g⁻¹. -1 This further demonstrates that the 0-dimensional carbon material fullerene selected in this invention has a significant effect on improving the fast-charging performance of batteries.

[0119] A comparison of Examples 9 and 10 with the example using carbon quantum dots shows that although fullerenes (C60), also a zero-dimensional carbon material, can coat and modify graphite to some extent at high temperatures, their localized stress and defect-inducing ability during pyrolysis are weaker than those of carbon quantum dots due to their highly closed and stable cage-like structure and lack of abundant oxygen-containing / heteroatom functional groups on the surface of carbon quantum dots. This further confirms that the preferred method of using carbon quantum dots as a modification precursor in this invention is the optimal choice for achieving deep lattice distortion at the graphite edge.

[0120] By comparing the electrochemical performance of Examples 1-10 with that of Example 11, it can be seen that ( Figure 7The composite material without high-temperature carbonization treatment (Example 11) not only failed to improve performance, but its energy storage performance was even worse than that of pure graphite (Comparative Example 1). This is because the carbon quantum dots without high-temperature pyrolysis are merely physically attached to the graphite surface. They cannot form a continuous, low-resistivity amorphous carbon coating layer, nor can they generate localized stress to induce graphite edge distortion to widen ion channels. Conversely, the surface of untreated carbon quantum dots contains a large number of insulating oxygen-containing functional groups. These functional groups not only hinder electron transport between graphite particles but also trigger numerous irreversible side reactions during the first charge-discharge process, consuming electrolyte and thus deteriorating the battery's initial coulombic efficiency and rate performance. Example 11 conversely confirms that the specific high-temperature carbonization process of this invention is an indispensable key synergistic step for eliminating undesirable functional groups, constructing an ultrathin carbon layer in situ, and inducing graphite edge distortion.

[0121] The rate test results of lithium iron phosphate assembled full cells were matched with those of Example 1 and Comparative Example 1, respectively. Figure 8 As can be seen, at an ultra-high discharge rate of 40 C, the discharge specific capacity of Example 1 is as high as 69.4 mAh g⁻¹. -1 It uses unmodified pure graphite (Comparative Example 1, 21.8 mAh g). -1 This demonstrates that the interface modification technology of this invention can still significantly improve the fast-charging dynamics of lithium-ion batteries in actual full-battery systems, and has extremely high practical application value.

[0122] The above are merely preferred embodiments of the present invention and do not limit the scope of patent protection of the present invention. Any equivalent structural, parameter, or procedural transformations made based on the content of this specification, or direct or indirect applications in other related technical fields (such as sodium / potassium ion batteries), are similarly included within the scope of patent protection of the present invention.

Claims

1. A zero-dimensional carbon material composite modified fast-charging graphite, characterized in that: When carbon quantum dots are used for modification, the modified fast-charging graphite has a crystalline graphite core inside, and its outer surface and edges are covered with an ultrathin amorphous carbon layer; furthermore, the edges of the modified graphite material have a lamellar curl and lattice distortion structure; the thickness of the ultrathin amorphous carbon layer is 1nm~10nm, and the ultrathin amorphous carbon layer is transformed from carbon quantum dots. When fullerene is used for modification, modified fast-charging graphite is obtained by uniformly mixing fullerene with graphite and then sintering it under a protective atmosphere.

2. The zero-dimensional carbon material composite modified fast-charging graphite according to claim 1, characterized in that: The thickness of the ultrathin amorphous carbon layer is 2nm-10nm, including thicknesses of 2nm-4nm, 2nm-6nm, 2nm-8nm, etc. Furthermore, the modified graphite material exhibits lamellar curling and lattice distortion structures at its edges; the ultrathin amorphous carbon layer is formed from carbon quantum dots.

3. The zero-dimensional carbon material composite modified fast-charging graphite according to claim 1, characterized in that: The parameters of the lattice distortion structure satisfy at least one of the following conditions: (1) In the Raman spectrum of the modified graphite material, the intensity ratio of the defect peak to the graphitization peak is 0.2 ~ 1.2; (2) In the X-ray diffraction pattern of the modified graphite material, the interlayer spacing of the (002) crystal plane is 0.3350 nm ~ 0.3380 nm.

4. The zero-dimensional carbon material composite modified fast-charging graphite according to claim 1, characterized in that: The carbon quantum dot high-temperature composite modified graphite material is prepared through the following steps: Carbon quantum dots are mixed with a graphite matrix in a set ratio to obtain a solid mixture; the solid mixture is placed in a protective atmosphere for high-temperature carbonization treatment, so that the carbon quantum dots are pyrolyzed in situ on the graphite surface and edges to obtain the carbon quantum dot high-temperature composite modified graphite material; wherein the mass ratio of carbon quantum dots to graphite matrix is ​​(1:50) to (1:10).

5. The zero-dimensional carbon material composite modified fast-charging graphite according to claim 4, characterized in that: The graphite matrix includes at least one of natural flake graphite, microcrystalline graphite, spherical graphite, mesophase carbon microspheres, or artificial graphite.

6. The zero-dimensional carbon material composite modified fast-charging graphite according to claim 4, characterized in that: The carbon quantum dots include undoped carbon quantum dots and / or heteroatom-doped carbon quantum dots; wherein the undoped carbon quantum dots mainly contain oxygen-containing functional groups on the surface, and the heteroatom-doped carbon quantum dots include carbon quantum dots doped with at least one element selected from nitrogen, sulfur, phosphorus or boron.

7. The zero-dimensional carbon material composite modified fast-charging graphite according to claim 1, characterized in that: The precursors for preparing the carbon quantum dots include at least one of citric acid, glucose, ascorbic acid, urea, thiourea, ethylenediamine, or biomass-derived carbon sources.

8. The zero-dimensional carbon material composite modified fast-charging graphite according to claim 4, characterized in that: The protective atmosphere includes one or more mixed gases selected from nitrogen, argon, or helium, with a gas flow rate of 50 mL / min to 200 mL / min.

9. The zero-dimensional carbon material composite modified fast-charging graphite according to claim 1, characterized in that: In the high-temperature carbonization process, the carbonization temperature is 800℃~1100℃; the carbonization time is 2h-6h.

10. An application of zero-dimensional carbon material composite modified fast-charging graphite as described in any one of claims 1-9, characterized in that: The zero-dimensional carbon material composite modified fast-charging graphite is used as the negative electrode active material of the electrochemical energy storage device, which includes a lithium-ion battery, a sodium-ion battery, or a potassium-ion battery.